Microcapsule adsorbent, preparation method thereof and application of microcapsule adsorbent in fabric after-finishing

By amine-modifying β-cyclodextrin and doping ammonium sulfate, a microcapsule adsorbent was formed, and the microcapsule adsorption and desorbed 2-nonenal was coated with organic liquid, which solved chitosan/β -The problem of desorption of cyclodextrin/sulfuramine composite particles after encountering water has significantly improved the deodorization performance of textiles.

CN119236885APending Publication Date: 2025-01-03LUOLAI LIFESTYLE TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409640.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Chitosan/β-cyclodextrin/sulfuramine complex particles undergo a reversible Schiff base reaction after encountering water, resulting in desorption of 2-nonenal and poor deodorization effect, especially in textile applications.

Method used

By amine-modifying the β-cyclodextrin and doping it with ammonium sulfate particles, a microcapsule adsorbent is formed, and the microcapsule adsorbent is coated with organic liquid to adsorb the desorbed 2-nonenal to prevent Its desorption improves adsorption performance.

Benefits of technology

It significantly improves the adsorption performance of 2-nonenal, effectively prevents its desorption, significantly improves the deodorization effect, and significantly improves the deodorization performance in textile applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236885A_ABST
    Figure CN119236885A_ABST
Patent Text Reader

Abstract

The invention relates to a microcapsule adsorbent, a preparation method thereof and application of the microcapsule adsorbent in fabric after-finishing. The preparation method comprises the following steps: S1, carrying out amino modification on beta-cyclodextrin to obtain modified beta-cyclodextrin; s2, mixing the modified beta-cyclodextrin and water, heating to dissolve the modified beta-cyclodextrin and water, and cooling to obtain a modified beta-cyclodextrin solution; adding an alcoholic solution of a liquid organic matter into the modified beta-cyclodextrin solution, stirring, refrigerating to precipitate, and carrying out solid-liquid separation to obtain a solid; the liquid organic matter is selected from liquid ester, liquid alcohol or a composition thereof; s3, ammonium sulfate doping: putting the solid into an ammonium sulfate aqueous solution, oscillating and drying. The beta-cyclodextrin is subjected to amino modification, and the ammonium sulfate particles are doped on the cyclodextrin, so that the effect of catalyzing the Schiff base reaction is achieved, and the directional adsorption and adsorption effect on the 2-nonenal are enhanced; 2-nonenal subjected to Schiff base reverse reaction desorption can be effectively adsorbed in organic liquid under the condition that the microcapsule encounters water, and desorption of 2-nonenal is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of textiles, and in particular to a microcapsule adsorbent and a preparation method thereof and application thereof in fabric finishing. Background Art

[0002] "Senior odor" refers to body odor that comes with aging. It is caused by the accumulation of dead skin due to factors such as slow skin metabolism, drugs, bad living habits, and secretion of special substances (the main component of "senior odor" is 2-nonanal). In most cases, "senior odor" is caused by skin aging. After skin aging, the sebaceous glands in the skin will oxidize faster and produce odor. The more active oxygen in the body, the more obvious the aging phenomenon and the heavier the odor. Active oxygen causes the sebaceous glands to oxidize, producing "senior odor" in the process. In addition, the sweat glands of the elderly have low function, so even if the amount of sweat is small, the skin will still emit odor.

[0003] In order to solve the problem of "senile odor", Chen Yonggen and others developed chitosan / β-cyclodextrin / thiosemicarbazide composite particles (CSCD-TSC). Specifically, epichlorohydrin and glutaraldehyde were used as cross-linking agents, and chitosan, β-cyclodextrin and thiosemicarbazide were coupled through chemical grafting and reverse emulsification to form CSCD-TSC composite particles.

[0004] However, the surface of chitosan / β-cyclodextrin / thiosemicarbazide composite particles (CSCD-TSC) is distributed with adsorption groups of hydroxyl and amino groups, which can adsorb 2-nonenal. The reversibility of the Schiff base reaction between the aldehyde group and the primary amine is not taken into account, especially the desorption phenomenon that occurs when wet. In particular, in the process of application to textiles, since nonenal is insoluble in water but easily soluble in organic solvents such as essential oils, it will react with primary amines to undergo a Schiff base reaction. The Schiff base reaction is a reversible reaction. When it encounters water, the reaction will turn to the reverse reaction and desorption will occur easily, resulting in poor deodorization effect. Summary of the invention

[0005] In view of the shortcomings of the prior art mentioned above, the present invention provides a microcapsule adsorbent and a preparation method thereof and application in fabric finishing to solve the technical problem that the chitosan / β-cyclodextrin / semicarbazide composite particles (CSCD-TSC) react to the reverse reaction after coming into contact with water and are prone to desorption, resulting in poor deodorization effect.

[0006] To achieve the above objectives, the scheme of this application is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a microcapsule adsorbent, characterized in that it comprises the following steps:

[0008] S1. Amino-modifying β-cyclodextrin to obtain modified β-cyclodextrin;

[0009] S2. Mixing modified β-cyclodextrin and water, heating to dissolve, and cooling to obtain a modified β-cyclodextrin solution;

[0010] Adding an alcohol solution of a liquid organic substance to the modified β-cyclodextrin solution, stirring, refrigerating to precipitate, and separating the solid from the liquid to obtain a solid; the liquid organic substance is selected from a liquid ester, a liquid alcohol, or a combination thereof;

[0011] S3. Doped with ammonium sulfate

[0012] The solid is placed in an aqueous solution of ammonium sulfate for shaking and drying to obtain the microcapsule adsorbent.

[0013] Optionally, in step S1, the amino modification of β-cyclodextrin comprises:

[0014] β-cyclodextrin and thiosemicarbazide are dispersed in water, and a glutaraldehyde aqueous solution is added dropwise to the water to perform a grafting reaction.

[0015] Optionally, in step S1, the mass ratio of β-cyclodextrin, thiosemicarbazide and glutaraldehyde is 8-12:4-5:0.9-1.5, preferably 9-12:4-4.8:0.9-1.4.

[0016] Optionally, in step S1, the grafting reaction is carried out for 2-4 hours, preferably 2.5-3.5 hours.

[0017] Optionally, in step S2, the material ratio of the liquid organic matter to the β-cyclodextrin is 1-1.5 mL: 8-12 g, preferably 1.1-1.5 mL: 9-12 g.

[0018] In the present application, in step S2, the liquid ester includes but is not limited to: mint oil.

[0019] In the present application, in step S2, the liquid alcohol includes but is not limited to: ethylene glycol.

[0020] Optionally, in step S3, the molar ratio of the ammonium sulfate to the β-cyclodextrin is 5-10:1-2.

[0021] In a second aspect, the present invention provides a microcapsule adsorbent prepared according to the method described above.

[0022] In a third aspect, the present invention provides a method for finishing a fabric, comprising the following steps:

[0023] The adhesive, the penetrant and the microcapsule adsorbent prepared according to the method described above are prepared into a finishing liquid;

[0024] The finishing liquid is used to perform padding, pre-drying, baking, washing and drying on the fabric to be treated.

[0025] Optionally, in the finishing liquid, the mass ratio of the adhesive, the penetrant and the microcapsule adsorbent is 45-55:1-5:45-55, preferably 58-65:1-4:48-55.

[0026] Optionally, in the finishing liquid, the concentration of the microcapsule adsorbent is 45-55 g / L, preferably 48-52 g / L.

[0027] Optionally, the pre-baking temperature is 65-75° C., preferably 68-72° C.; the pre-baking time is 2-5 min, preferably 3-5 min.

[0028] Optionally, the baking temperature is 115-125° C., preferably 118-123° C.; the baking time is 2-5 min, preferably 3-5 min.

[0029] Optionally, the mass ratio of the fabric to be treated to the finishing liquid is 1:10-15, preferably 1:12-15.

[0030] In a fourth aspect, the present invention provides a fabric prepared according to the method as described above.

[0031] In a fifth aspect, the present invention provides a method for preparing a fabric, including the finishing method as described above.

[0032] Beneficial effects of the present invention:

[0033] The present application uses β-cyclodextrin to perform amino modification, and dopes ammonium sulfate particles on the cyclodextrin to catalyze the Schiff base reaction, thereby enhancing the directional adsorption and adsorption effect of 2-nonenal. Since the microcapsule adsorbent is coated with an organic liquid, the 2-nonenal desorbed due to the Schiff base reverse reaction can be effectively adsorbed in the organic liquid when the microcapsule adsorbent meets water, thereby achieving the purpose of effectively preventing the desorption of 2-nonenal, thereby significantly improving the adsorption performance of 2-nonenal. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the present invention. DETAILED DESCRIPTION

[0035] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0036] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0037] like Figure 1 As shown, one embodiment of the present invention provides a method for preparing a microcapsule adsorbent, comprising the following steps:

[0038] S1. Amino modification of β-cyclodextrin: β-cyclodextrin and thiosemicarbazide are dispersed in water, and glutaraldehyde aqueous solution is added dropwise to the water to carry out grafting reaction for 2-4 hours to obtain modified β-cyclodextrin; the mass ratio of β-cyclodextrin, thiosemicarbazide and glutaraldehyde is 8-12:4-5:0.9-1.5;

[0039] S2. Mixing modified β-cyclodextrin and water, heating to dissolve, and cooling to obtain a modified β-cyclodextrin solution;

[0040] Adding an alcohol solution of a liquid organic substance into a modified β-cyclodextrin solution, stirring, refrigerating to precipitate, and separating the solid from the liquid to obtain a solid; the liquid organic substance is selected from a liquid ester, a liquid alcohol, or a combination thereof;

[0041] The material ratio of liquid organic matter to β-cyclodextrin is 1-1.5mL:8-12g;

[0042] S3. Doping with ammonium sulfate: placing the solid in an aqueous solution of ammonium sulfate, shaking it, and drying it to obtain the microcapsule adsorbent, wherein the molar ratio of ammonium sulfate to β-cyclodextrin is 5-10:1-2.

[0043] By modifying the β-cyclodextrin with amino groups (processed by step S1) and doping the cyclodextrin with ammonium sulfate particles (processed by step S3), the Schiff base reaction is catalyzed to enhance the directional adsorption and adsorption effect of 2-nonenal. Since the microcapsule adsorbent is coated with an organic liquid (processed by step S2), the 2-nonenal desorbed due to the Schiff base reverse reaction can be effectively adsorbed in the organic liquid when the microcapsule adsorbent meets water, thereby effectively preventing the desorption of 2-nonenal and significantly improving the adsorption performance of 2-nonenal.

[0044] Another embodiment of the present invention provides a microcapsule adsorbent prepared according to the method described above.

[0045] Another embodiment of the present invention further provides a fabric finishing method, comprising the following steps:

[0046] The binder, the penetrant and the microcapsule adsorbent prepared according to the above method are prepared into a finishing liquid with a concentration of 45-55 g / L of the microcapsule adsorbent according to a mass ratio of 45-55:1-5:45-55;

[0047] The fabric to be treated is impregnated with a finishing liquid, pre-dried, baked, washed and dried. The pre-dried temperature is 65-75°C and the baking temperature is 115-125°C.

[0048] Another embodiment of the present invention also provides a fabric made according to the method as described above.

[0049] Another embodiment of the present invention further provides a method for preparing a fabric, including the post-finishing method as described above.

[0050] In the following description, numerous details are discussed to provide a more thorough explanation of embodiments of the present invention; however, it is apparent to one skilled in the art that embodiments of the present invention may be practiced without these specific details.

[0051] Example 1

[0052] A cotton fabric post-finishing method, the specific steps are as follows:

[0053] S1. Amino modification of β-cyclodextrin: 20 g of β-cyclodextrin and 8.8 g of thiosemicarbazide were dispersed in 200 mL of water, and the mixture was shaken at a constant temperature for 30 min. During the constant temperature shaking process, a 25 wt% glutaraldehyde aqueous solution was slowly added dropwise to the water to carry out a grafting reaction for 3 h. The mixture was filtered, and the solid obtained by filtration was washed with anhydrous ethanol to obtain modified β-cyclodextrin. The mass ratio of β-cyclodextrin, thiosemicarbazide and glutaraldehyde was 10:4.1:1.12.

[0054] S2. Mix 12 g of modified β-cyclodextrin and 180 mL of deionized water, heat (not exceeding 70 ° C) and stir to dissolve, and cool the solution after clarification to obtain a modified β-cyclodextrin solution;

[0055] Dissolving peppermint oil in an ethanol aqueous solution having a volume concentration of 10% to obtain an alcohol solution of peppermint oil;

[0056] Slowly add the alcohol solution of peppermint oil to the modified β-cyclodextrin solution, stir at 65°C for 24 hours, refrigerate at 4°C overnight to precipitate, filter under vacuum, and wash the precipitate three times with anhydrous ethanol to obtain a solid;

[0057] The material ratio of peppermint oil to β-cyclodextrin is 1.15mL:10g;

[0058] S3. Doped with ammonium sulfate

[0059] The solid washed in step S2 is placed in a 10 wt% ammonium sulfate aqueous solution and shaken for 10 minutes, and then placed in an oven for drying to obtain a microcapsule adsorbent, wherein the molar ratio of ammonium sulfate to β-cyclodextrin is 6:1.5;

[0060] S4. The binder Goon720, the penetrant JFC and the microcapsule adsorbent were prepared into a finishing liquid having a concentration of 50 g / L of the microcapsule adsorbent according to a mass ratio of 50:2:50, and the solvent used was water;

[0061] S5. Cut the cotton fabric into samples of 10cm*10cm size, immerse the samples in the finishing liquid for 1h (the mass ratio of sample to finishing liquid is 1:12), use a table padder to dip and roll twice (liquid carrying rate 100%), place the impregnated and rolled samples in an oven at 70℃ for pre-baking for 3min, then bake at 120℃ for 3min, then wash with deionized water, and dry at low temperature to obtain the finished fabric.

[0062] Example 2

[0063] A cotton fabric post-finishing method, the specific steps are as follows:

[0064] S1. Amino modification of β-cyclodextrin: 24 g β-cyclodextrin and 10 g semicarbazide were dispersed in 250 mL water, and the mixture was shaken at a constant temperature for 30 min. During the constant temperature shaking process, a 25 wt% glutaraldehyde aqueous solution was slowly added dropwise to the water to carry out a grafting reaction for 4 h. The mixture was filtered, and the solid obtained by filtration was washed with anhydrous ethanol to obtain modified β-cyclodextrin. The mass ratio of β-cyclodextrin, semicarbazide and glutaraldehyde was 12:5:0.9.

[0065] S2. Mix 12 g of modified β-cyclodextrin and 180 mL of deionized water, heat (not exceeding 70 ° C) and stir to dissolve, and cool the solution after clarification to obtain a modified β-cyclodextrin solution;

[0066] Dissolving ethylene glycol in an ethanol aqueous solution having a volume concentration of 10% to obtain an ethylene glycol alcohol solution;

[0067] Slowly add the alcohol solution of ethylene glycol to the modified β-cyclodextrin solution, stir at 70°C for 24 hours, refrigerate at 4°C overnight to precipitate, filter under vacuum, and wash the precipitate three times with anhydrous ethanol to obtain a solid;

[0068] The material ratio of ethylene glycol to β-cyclodextrin is 1mL:12g;

[0069] S3. Doped with ammonium sulfate

[0070] The solid washed in step S2 is placed in an aqueous solution of ammonium sulfate with a concentration of 10 wt% and shaken for 10 minutes, and then placed in an oven for drying to obtain a microcapsule adsorbent, wherein the molar ratio of ammonium sulfate to β-cyclodextrin is 7:2;

[0071] S4. The binder Goon720, the penetrant JFC and the microcapsule adsorbent were prepared into a finishing liquid with a concentration of 55 g / L of the microcapsule adsorbent according to a mass ratio of 45:1:55, and the solvent used was water;

[0072] S5. Cut the cotton fabric into samples of 10cm*10cm size, immerse the samples in the finishing liquid for 1h (the mass ratio of sample to finishing liquid is 1:15), use a table padder to dip and roll twice (liquid carrying rate 100%), place the impregnated and rolled samples in an oven at 75℃ for pre-baking for 2min, then bake at 115℃ for 5min, then wash with deionized water, and dry at low temperature to obtain the finished fabric.

[0073] Example 3

[0074] A cotton fabric post-finishing method, the specific steps are as follows:

[0075] S1. Amino modification of β-cyclodextrin: 16 g β-cyclodextrin and 8 g semicarbazide were dispersed in 180 mL water, and the mixture was shaken at a constant temperature for 30 min. During the constant temperature shaking process, a 25 wt% glutaraldehyde aqueous solution was slowly added dropwise to the water to carry out a grafting reaction for 2-4 h. The mixture was filtered, and the solid obtained by filtration was washed with anhydrous ethanol to obtain modified β-cyclodextrin. The mass ratio of β-cyclodextrin, semicarbazide and glutaraldehyde was 8:4:1.5.

[0076] S2. Mix 12 g of modified β-cyclodextrin and 180 mL of deionized water, heat (not exceeding 70 ° C) and stir to dissolve, and cool the solution after clarification to obtain a modified β-cyclodextrin solution;

[0077] Dissolving peppermint oil in an ethanol aqueous solution having a volume concentration of 10% to obtain an alcohol solution of peppermint oil;

[0078] Slowly add the alcohol solution of peppermint oil to the modified β-cyclodextrin solution, stir at 60°C for 24 hours, refrigerate at 4°C overnight to precipitate, filter under vacuum, and wash the precipitate three times with anhydrous ethanol to obtain a solid;

[0079] The material ratio of peppermint oil to β-cyclodextrin is 1.5 mL: 8 g;

[0080] S3. Doped with ammonium sulfate

[0081] The solid washed in step S2 is placed in a 10 wt % ammonium sulfate aqueous solution and shaken for 10 min, and then placed in an oven for drying to obtain a microcapsule adsorbent, wherein the molar ratio of ammonium sulfate to β-cyclodextrin is 10:1;

[0082] S4. The binder Goon720, the penetrant JFC and the microcapsule adsorbent were prepared into a finishing liquid having a concentration of 45 g / L of the microcapsule adsorbent according to a mass ratio of 55:5:45, and the solvent used was water;

[0083] S5. Cut the cotton fabric into samples of 10cm*10cm size, immerse the samples in the finishing liquid for 1h (the mass ratio of sample to finishing liquid is 1:10), use a table padder to dip and roll twice (liquid carrying rate 100%), place the impregnated and rolled samples in an oven at 65℃ for pre-baking for 5min, then bake at 25℃ for 2min, then wash with deionized water, and dry at low temperature to obtain the finished fabric.

[0084] Comparative Example 1

[0085] The cotton fabric was post-finished in the same manner as in Example 1 except for the following conditions:

[0086] S3. Doped with ammonium sulfate

[0087] The modified β-cyclodextrin in step S1 was placed in a 10 wt % ammonium sulfate aqueous solution and shaken for 10 minutes, and then placed in an oven for drying to obtain a microcapsule adsorbent, wherein the molar ratio of ammonium sulfate to β-cyclodextrin was 6:1.5.

[0088] That is, this comparative example is not coated with an organic liquid.

[0089] Comparative Example 2

[0090] The cotton fabric was post-finished in the same manner as in Example 1 except for the following conditions:

[0091] S4. The adhesive Goon720, the penetrant JFC and the solid after cleaning in step S2 were prepared into a finishing liquid with a concentration of 50 g / L of the solid after cleaning in micro-step S2 according to a mass ratio of 50:2:50, and the solvent used was water.

[0092] That is, in this comparative example, β-cyclodextrin was not doped with ammonium sulfate.

[0093] Performance Testing

[0094] The deodorizing performance of Example 1 and Comparative Examples 1-2 on 2-nonenal was tested, and the specific steps were as follows:

[0095] A closed cabinet with a size of 420*480*640mm was selected, and a trans-2-nonenal petroleum ether solution with a mass concentration of 0.30mg / mL was prepared and placed in a closed environment so that the closed cabinet was filled with trans-2-nonenal gas. The sample to be tested was added before sealing, and the adsorption experiment was carried out at a constant temperature of 25°C. After 0.5h, 1h, 1.5h, 2.0, and 2.5h, the absorbance of the trans-2-nonenal petroleum ether solution in the adsorption device at an ultraviolet wavelength of 226nm was measured respectively, and the residual concentration of the trans-2-nonenal petroleum ether solution was calculated according to the linear regression equation. A blank control group was set up. The blank control group had the same conditions except that the finished fabric was not placed therein, and the adsorption amount was calculated according to the following formula:

[0096]

[0097] Wherein, λ is the adsorption amount, in mg / g; V is the volume of trans-2-nonenal petroleum ether solution, in mL; ρ0 is the initial concentration of trans-2-nonenal petroleum ether solution, in mg / mL; ρ1 is the remaining calibration total concentration of trans-2-nonenal petroleum ether solution in the blank control group, in mg / mL; m is the mass of the finished fabric, in g;

[0098] The fabrics after finishing in Example 1 and Comparative Example 1 were placed in water and soaked, and then the deodorizing performance of Example 1 and Comparative Example 1 on 2-nonenal was tested again according to the above method. The results are shown in Table 1.

[0099] Table 1 Test results

[0100]

[0101] As shown in Table 1, compared with Comparative Examples 1-2, after a period of time, the adsorption amount of the fabric of Example 1 increased significantly; and there was no significant difference in the adsorption amount between Example 1 (dry sample) and Example 1 (wet sample). The results show that the present application uses β-cyclodextrin for amino modification and doping ammonium sulfate particles on cyclodextrin to catalyze the Schiff base reaction, enhance the directional adsorption and adsorption effect of 2-nonenal, and because the microcapsule microcapsule adsorbent is coated with an organic liquid, the 2-nonenal that is desorbed due to the reverse reaction of the Schiff base can be effectively adsorbed in the organic liquid when the microcapsule microcapsule adsorbent is in contact with water, so as to effectively prevent the desorption of 2-nonenal, thereby significantly improving the adsorption performance of 2-nonenal.

[0102] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a microcapsule adsorbent, characterized in that: The following steps are involved: S1. Amino-modifying β-cyclodextrin to obtain modified β-cyclodextrin; S2. Mixing modified β-cyclodextrin and water, heating to dissolve, and cooling to obtain a modified β-cyclodextrin solution; Adding an alcohol solution of a liquid organic substance into the modified β-cyclodextrin solution, stirring, refrigerating to precipitate, and separating the solid from the liquid to obtain a solid; the liquid organic substance is selected from a liquid ester, a liquid alcohol, or a combination thereof; S3. Doped with ammonium sulfate The solid is placed in an aqueous solution of ammonium sulfate for shaking and drying to obtain the microcapsule adsorbent.

2. The method for preparing a microcapsule adsorbent according to claim 1, characterized in that: In step S1, the amino modification of β-cyclodextrin includes: β-cyclodextrin and thiosemicarbazide are dispersed in water, and a glutaraldehyde aqueous solution is added dropwise to the water to perform a grafting reaction.

3. The method for preparing a microcapsule adsorbent according to claim 2, characterized in that: In step S1, the mass ratio of β-cyclodextrin, thiosemicarbazide and glutaraldehyde is 8-12:4-5:0.9-1.5; And / or, in step S1, the grafting reaction duration is 2-4 hours.

4. The method for preparing a microcapsule adsorbent according to claim 1, characterized in that: In step S2, the material ratio of the liquid organic matter to the β-cyclodextrin is 1-1.5 mL: 8-12 g.

5. The method for preparing a microcapsule adsorbent according to claim 1, characterized in that: In step S3, the molar ratio of the ammonium sulfate to the β-cyclodextrin is 5-10:1-2.

6. A microcapsule adsorbent prepared according to the method according to any one of claims 1 to 5.

7. A fabric finishing method, characterized in that: The following steps are involved: Prepare a finishing liquid by mixing an adhesive, a penetrant and a microcapsule adsorbent prepared according to the method of any one of claims 1 to 5; The finishing liquid is used to perform padding, pre-drying, baking, washing and drying on the fabric to be treated.

8. The fabric finishing method according to claim 7, characterized in that: In the finishing liquid, the mass ratio of the adhesive, the penetrant and the microcapsule adsorbent is 45-55:1-5:45-55; and / or, in the finishing liquid, the concentration of the microcapsule adsorbent is 45-55 g / L; And / or, the pre-baking temperature is 65-75° C., and the pre-baking time is 2-5 min; And / or, the baking temperature is 115-125° C., and the baking time is 2-5 min.

9. The fabric prepared according to the method of claim 7 or 8.

10. A method for preparing a fabric, characterized in that: The method comprises the finishing method described in claim 7 or 8.